Serum ionic magnesium in traumatic brain injury - Dhandapani, SS; Gupta, Aditya; Vivekanandhan, S; Mahapatra, AK; Mehta, VS (Indian Journal of Neurotrauma, 2005)
Magnesium is an important ion in the body milieu, being a component of several enzymatic processes in the intra- and extracellular compartments. We have compared serum ionic magnesium levels between patients of severe closed traumatic brain injury and normal volunteers, so as to correlate the magnesium levels to severity of head injury. The study was carried out on fifty four patients of closed head injury with GCS 5–8. Biochemical analysis of serum for ionic magnesium was done at admission. The test was also performed on 20 normal volunteers and the results were studied for significant differences. Magnesium levels were compared between various subgroups defined by age, sex, admission interval, alcohol dependence, GCS, CT findings and appropriate statistical analyses done. Serum ionic magnesium levels in patients of severe head injury were in the range 0.15 to 0.45 mmol/ L (Mean 0.37 mmol/L) as compared with control range 0.4 to 0.6 mmol/L (Mean 0.44 mmol/L) which was statistically significant. Additionally it was found that patients presenting earlier than 6 hrs had significantly lower serum ionic magnesium levels compared with those presenting later. Other subgroup differences were not statistically significant. Admission serum ionic magnesium levels of patients with severe closed TBI appear to be significantly lower than those of normal controls, more so within the first 6 hours after injury.
Keywords: brain injury; Glasgow Coma Scale; head injury; serum magnesium